Effects of chronic caffeine consumption on sleep and the sleep electroencephalogram in mice. (January 2019) - Panagiotou, Maria; Meijer, Mandy; Meijer, Johanna H; Deboer, Tom
Background: Caffeine is one of the most widely consumed psychostimulants, and it impacts sleep and circadian physiology. Aim: Caffeine is generally used chronically on a daily basis. Therefore, in the current study, we investigated the chronic effect of caffeine on sleep in mice. Methods: We recorded the electroencephalogram and electromyogram on a control day, on the first day of caffeine consumption (acute), and following two weeks of continuous caffeine consumption (chronic). In the latter condition, a period of six-hour sleep deprivation was conducted during the light period. Control mice, which received normal drinking water, were also recorded and sleep deprived. Results: We found that caffeine induced differential effects following acute and chronic consumption. Over 24 h, waking increased following acute caffeine whereas no changes were found in the chronic condition. The daily amplitude of sleep–wake states increased in both acute and chronic conditions, with the highest amplitude in the chronic condition, showing an increase in sleep during the light and an increase in waking during the dark. Furthermore, electroencephalogram slow-wave-activity in non-rapid eye-movement sleep was increased, compared with both control conditions, during the first half of the light period in the chronic condition. It was particularly challenging to keep the animals awake during the sleep deprivation period under chronic caffeine. Conclusions: Together the data suggest an increased sleep pressure under chronic caffeine. In contrast to the traditional conception on the impact on sleep, chronic caffeine intake seems to increase the daily sleep–wake cycle amplitude and increase sleep pressure in mice.